Right-wing populism in America : too close for comfort - Berlet, Chip, 1949-; Lyons, Matthew Nemiroff (New York : Guilford Press, 2000)
Right-wing militias and other antigovernment organizations have received heightened public attention since the Oklahoma City bombing. While such groups are often portrayed as marginal extremists, the values they espouse have influenced mainstream politics and culture far more than most Americans realize. This important volume offers an in-depth look at the historical roots and current landscape of right-wing populism in the United States. Illuminated is the potent combination of anti-elitist rhetoric, conspiracy theories, and ethnic scapegoating that has fueled many political movements from the colonial period to the present day. The book examines the Jacksonians, the Ku Klux Klan, and a host of Cold War nationalist cliques, and relates them to the evolution of contemporary electoral campaigns of Patrick Buchanan, the militancy of the Posse Comitatus and the Christian Identity movement, and an array of millennial sects. Combining vivid description and incisive analysis, Berlet and Lyons show how large numbers of disaffected Americans have embraced right-wing populism in a misguided attempt to challenge power relationships in U.S. society. Highlighted are the dangers these groups pose for the future of our political system and the hope of progressive social change.
Introduction -- 1. Rebellious Colonizers: Bacon's Rebellion and the American Revolution -- 2. The Real People: Antimasonry, Jacksonianism, and Anti-Catholic Nativism -- 3. A Great Mongrel Military Despotism: The First Ku Klux Klan and the Anti-Chinese Crusade -- 4. Barbarians and Plunder Leagues: Theodore Roosevelt and the Progressives -- 5. 100 Percent Americanism: World War I-Era Repression and the Second Ku Klux Klan -- 6. The Industrialist as Producer: Henry Ford's Corporate Empire -- 7. Driving Out the Money Changers: Fascist Politics in the New Deal Era -- 8. From New Deal to Cold War: Political Scapegoating and Business Conflict from the 1930s to the 1950s -- 9. The Pillars of U.S. Populist Conspiracism: The John Birch Society and the Liberty Lobby -- 10. From Old Right to New Right: Godless Communism, Civil Rights, and Secular Humanism -- 11. Culture Wars and Political Scapegoats: Gender, Sexuality, and Race -- 12. Dominion Theology and Christian Nationalism: Hard-Line Ideology versus Pragmatism -- 13. New Faces for White Nationalism: Reframing Supremacist Narratives -- 14. Battling the New World Order: Patriots and Armed Militias -- 15. The Vast Clinton Conspiracy Machine: The Hard Right on the Center Stage -- 16. The New Millennium: Demonization, Conspiracism, and Scapegoating in Transition -- Conclusions.
Includes bibliographical references (p. 421-471) and index.
The Roger Griffin ComFas Collection
Keywords: Conservatism -- United States; Right-wing extremists -- United States; Populism -- United States